2020
DOI: 10.3390/ijerph17093276
|View full text |Cite
|
Sign up to set email alerts
|

Comet Test in Saliva Leukocytes of Pre-School Children Exposed to Air Pollution in North Italy: The Respira Study

Abstract: Air pollution is a well-known problem for human health, especially for children living in highly polluted urban areas. This study aimed to assess the relationship between airborne pollutants concentration and biomarkers of DNA damage in the buccal mucosa cells of pre-school children. DNA damage was investigated with comet test in saliva leukocytes taken from sputum of 3- to 6-year-old children living in Brescia, Northern Italy, collected during two consecutive winter seasons (2012–2013). The daily levels of PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…First, we successfully yielded a suitable number of viable cells, widely sufficient to perform the comet assay. Overall, tail intensity detected in oral mononuclear leukocytes was comparable [ 56 ] or lower than that reported in other studies, in both control and exposed subjects [ 51 , 55 ]. Another work [ 52 ] used visual scoring approach, grading different levels of DNA damage from 0 to 4, where 4 was the most severe damage for each comet visualized.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…First, we successfully yielded a suitable number of viable cells, widely sufficient to perform the comet assay. Overall, tail intensity detected in oral mononuclear leukocytes was comparable [ 56 ] or lower than that reported in other studies, in both control and exposed subjects [ 51 , 55 ]. Another work [ 52 ] used visual scoring approach, grading different levels of DNA damage from 0 to 4, where 4 was the most severe damage for each comet visualized.…”
Section: Discussionsupporting
confidence: 75%
“…have not always been investigated [ 51 ], or, in other cases, the number of non-exposed subjects was somehow limited [ 52 , 53 ]. Besides, some of those studies used cryopreserved samples [ 54 , 55 ] while others specifically focused attention in pre-school children [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study is the conclusion of the RESPIRA project that assessed the correlation between air pollution and early biological effects in exposed children. The chemical composition of PM and its genotoxicity and the MN and comet tests on children’s buccal mucosa cells have been reported in previous publications [ 16 , 23 , 26 ].…”
Section: Introductionmentioning
confidence: 95%
“…This study is the conclusion of the RESPIRA project that assessed the correlation between air pollution and early biological effects in exposed children. The chemical composition of PM and its genotoxicity and the MN and comet tests on children's buccal mucosa cells have been reported in previous publications [16,23,26]. This paper aims to assess the relationships between the concentration and toxic equivalency of polycyclic aromatic hydrocarbons (PAHs) in different sized PM fractions collected near the schools attended by children and air sample genotoxicity and micronuclei and DNA damage (comet test) in children's buccal mucosa cells.…”
Section: Introductionmentioning
confidence: 97%
“…McCauley et al ( 2008 ) found increased DNA damage in salivary leucocytes (isolated by density gradient centrifugation) of agricultural workers compared to controls. And Zani et al ( 2020 ) evaluated the effects of air pollution in salivary leucocytes (directly obtained from mouthwashes, without isolation) of exposed pre-school children, observing no significant association between air pollution and DNA damage. Furthermore, although buccal leucocytes obtained from smokers and analysed by the comet assay were reported to have more DNA damage than cells from non-smokers (Oßwald et al 2003 ), more recent studies showed that comet parameters evaluated in salivary leucocytes are not influenced by sex, age, smoking habit, diet, alcohol consumption or body mass index (McCauley et al 2008 ; Russo et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%